The Vampire in the Next Cubicle: The Americans with Disabilities Act and the Undead - Prottas, David J. (Employee responsibilities and rights journal, 2012)
Vampires are increasingly participating, and being visible, in American society. Their emergence from the shadows and entrance into mainstream activities, such as employment, brings new challenges for organizations and individuals. This article is intended to serve as a guide to human resource and general managers of the impact of the American with Disabilities Act (ADA) on the employment of individuals who are vampires or, believe themselves to be vampires. It demonstrates that organizations which discriminate against vampires based solely upon myths, stereotypes and prejudices may face legal consequences. The analysis of the specific subject of vampirism is also intended to provide an overview of the issues related to the application of the ADA in general.